Talking nets : an oral history of neural networks - Anderson, James A.; Rosenfeld, Edward (MIT Press, 1998)
Surprising tales from the scientists who first learned how to use computers to understand the workings of the human brain.
"A Bradford book."
Keywords: Neural computers.; Neural networks (Computer science); Scientists -- Interviews.; Science.; Pattern recognition systems.; Physical sciences.; Artificial intelligence.; Neural Networks, Computer; Science; Pattern Recognition, Automated; Natural Science Disciplines; Artificial Intelligence; Mathematical Concepts; Phenomena and Processes; Information Science; Disciplines and Occupations; Computing Methodologies; Ordinateurs neuronaux.; Réseaux neuronaux (Informatique); Scientifiques -- Entretiens.; Sciences.; Reconnaissance des formes (Informatique); Sciences physiques.; Intelligence artificielle.; sciences (philosophy); physical sciences.; artificial intelligence.; science (modern discipline); COMPUTERS -- Neural Networks.; Physical sciences; Pattern recognition systems; Artificial intelligence; Neural computers; Scientists; Neurale netwerken.; Interview; interviews.; Interviews; Interviews (vorm); Interviews.